2007
DOI: 10.1002/cncr.23068
|View full text |Cite
|
Sign up to set email alerts
|

Placement of radiopaque clips for tumor localization in patients undergoing neoadjuvant chemotherapy and breast conservation therapy

Abstract: An electropolymerization of haloalkylhalosilanes (ClRSiCH3Cl2) that possess two types of electroactive sites, that is, the CCl and SiCl bond is described. The one‐pot synthesis method is shown to yield branched polycarbosilanes having a regular carbon block‐spaced silicon backbone structure. A series of branched polycarbosilanes, [RSiCH3]n with R being CH2, C2H4, C3H6, and CH2C6H4C2H4, have been successfully electropolymerized with Mn up to 42,600 Dalton. Experimental and simulation cyclic vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
56
0
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 98 publications
(60 citation statements)
references
References 33 publications
0
56
0
4
Order By: Relevance
“…a retrospective review was done of 373 patients undergoing preoperative chemotherapy followed by lumpectomy to evaluate the need for marker placement. [8] Of the 373 patients studied, 145 had radiopaque markers placed and 228 did not. With a follow up of approximately 4 years, the patients with marker placement had an improved rate of local control versus those that did not have a marker placed (98.6% v 91.7%, P=0.02).…”
Section: Tumor Localizationmentioning
confidence: 99%
“…a retrospective review was done of 373 patients undergoing preoperative chemotherapy followed by lumpectomy to evaluate the need for marker placement. [8] Of the 373 patients studied, 145 had radiopaque markers placed and 228 did not. With a follow up of approximately 4 years, the patients with marker placement had an improved rate of local control versus those that did not have a marker placed (98.6% v 91.7%, P=0.02).…”
Section: Tumor Localizationmentioning
confidence: 99%
“…For individuals who are suitable operative candidates, a meta-analysis of nine randomized studies which included 3,946 patients comparing PST with adjuvant chemotherapy showed no difference in recurrence or survival, although PST was associated with an increased risk of loco-regional recurrence [90]. Radio opaque clip placement prior to PST is associated with a lower local recurrence rate in patients who are candidates for breast conservation [91]. Disease is less likely to recur in individuals who exhibit a pathologic complete response (pCR) in the breast [92] or breast and lymph nodes [93,94], making this a short-term surrogate that is potentially useful for predicting long-term outcomes.…”
Section: Preoperative Neoadjuvant Systemic Therapymentioning
confidence: 99%
“…Some studies have shown higher local recurrence rates with breast conservation after neoadjuvant chemotherapy, which may be in part related to difficulty in localizing the tumor by examination or imaging, or tumors that decrease in size in a honey-comb pattern rather than a concentric pattern. Some have advocated placement of clips in the tumor bed prior to (or during) neoadjuvant therapy, which has resulted in improved local control rates in some retrospective studies [49].…”
Section: Surgery After Neoadjuvant Therapymentioning
confidence: 99%